Analysis of Soil Quality as Hydrological Disaster Mitigation Efforto in Krueng Jreue Sub-Watershed, Great Aceh (retracted due to double publication) - Helmi Helmi; Hairul Basri; Sufardi Sufardi; Helmi Helmi (Aceh International Journal of Science and Technology, 2017)
This paper is retracted by editor due to publication ethics missconducted by author (simultaneously publication in other journal).